Risk factors for hospital norovirus outbreaks: impact of vomiting, genotype, and multi-occupancy rooms. Issue 4 (April 2018) - Fraenkel, CJ.; Inghammar, M.; Söderlund-Strand, A.; Johansson, P.J.H.; Böttiger, B.
Summary: Background: Norovirus is frequently introduced to the hospital and is a frequent cause of hospital outbreaks. Recognition of the factors that facilitate or impede norovirus transmission is an important step to effectively prevent hospital outbreaks. Aim: To investigate risk factors for norovirus outbreaks in hospital settings. Methods: Clinical data, ward setting, and norovirus genotype were collected from all 65 norovirus-positive index cases in outbreaks and all 186 sporadic norovirus cases at 192 wards in southern Sweden during 2010–2012 in a nested case–control study. Uni- and multivariate statistical analyses were conducted. Findings: Outbreak was independently associated with the number of patients sharing a room with the norovirus case (odds ratio (OR): 1.9 per additional patient in the room; P < 0.01), vomiting (OR: 2.6; P = 0.04), age >80 years (OR: 3.2; P < 0.01), comorbidity (OR: 2.3; P = 0.05), and onset of symptoms after admission to the ward (OR: 3.5; P < 0.01) in the multivariate analysis. Infection with genotype GII.4 was found to be strongly associated with outbreak in the univariate analysis (OR: 5.7; P < 0.01). Moreover, associations between GII.4 and vomiting (OR: 2.5; P = 0.01) and old age (OR: 4.3: P < 0.01) were found. Conclusion: This is the first study to investigate clinical, ward and genotype risk factors for norovirus hospital outbreaks. Recognition of these factors may help direct and prioritize infection control actions based on the outbreak risk. The results also suggest that the outbreak association with GII.4 partly may be explained by an enhanced ability to induce vomiting.